Entrepreneurship, gender and job creation. European dynamics - Cowling, Marc (Brighton, 2008)
"Since the seminal Birch job creation study (1979), policy-makers across the world have been keen to promote entrepreneurship as a mechanism for creating new employment opportunities. In parallel with this political desire, researchers have sought to isolate what types of people become entrepreneurs and what types of entrepreneurs create the most jobs. At the basic level, we observe that men constitute the majority of the total entrepreneurial stock. But our research finds that (a) much of the observed differential is easily accounted for by differences in sector and occupational characteristics of men and women, and (b) the true gender difference is diminishing rapidly over time. But it still remains the case that male entrepreneurs have a 9.5 per cent higher probability of creating jobs. However, in certain countries, notably Germany and Denmark, female entrepreneurs have an impressive record of job creation."